382 IMPACT OF PREOPERATIVE RADIOTHERAPY ON LYMPH NODE HARVEST IN RECTAL CARCINOMA. (1st January 2006) - Wiktor, A. J.; Pearlman, N.; McCarter, M.
Abstract : Purpose: Consensus guidelines indicate that the number of lymph nodes (LN) harvested in rectal carcinoma is critical to cancer staging accuracy and to subsequent treatment. Preoperative radiotherapy (PRT) has become a standard of care, yet its use may decrease the number of LN available for pathological evaluation. The aim of this investigation was to determine if PRT reduced the number of LN evaluated and assess how this might influence overall treatment and survival. Methods: Regional data from a statewide tumor registry were obtained from 954 rectal carcinoma cases diagnosed between 1996 and 2003. A more recent data set was obtained from 24 patients treated at a university hospital (UH) between 2001 and 2005. Information gathered included tumor and patient characteristics as well as use of PRT, number of LN evaluated, and follow-up information when available. Statistical analysis was performed by Student's t -test and chi-square where indicated. Results: Lymph node information was available from 827 patients (86%). Of these, 104 patients (12%) received preoperative RT, whereas 728 patients (88%) did not. Significantly fewer LN were pathologically examined in patients who had received PRT (mean 5.5 nodes vs 9.9 nodes, p ≤ .01). In the UH study group 16 patients (67%) underwent PRT, whereas 8 patients (33%) did not. Significantly fewer LN were examined in patients who received PRT (8.4 nodes vs 13.3 nodes, p ≤ .05). However, there was no significant difference in numbers of positive LN discovered (PRT 2.5 nodes vs 3.6 nodes, p = .13). Tumor size was significantly smaller in the PRT group (2.8 cm vs 4.8 cm, p ≤ .05). PRT resulted in a reduction of T stage in 25% of patients. Conclusion: PRT resulted in significantly smaller tumors, but at the cost of significantly fewer LN evaluated. The impact of this observation on overall survival awaits further analysis of long-term follow-up data.